Mengapa Pengguna Tetap Menggunakan Halodoc? Analisis Faktor-Faktor Pembentuk Nilai Persepsian - Rahma Sarita; Didik Setyawan; Ariefah Yulandari; Yulianto Yulianto (Jurnal Bisnis dan Kewirausahaan, 2025)
ABSTRACT This study aims to examine the influence of perceived value on the intention to continue using the Halodoc app. The intention to continue using the Halodoc app is influenced by the perceived value of the app. Perceived value impacts the intention to continue using the Halodoc app. Data were obtained through a questionnaire distributed to the general public who had previously used the Halodoc app. A total of 236 people were sampled. The sampling technique used was purposeful sampling. Hypothesis testing was conducted using SEM (Structural Equation Modeling) analysis with path analysis. The results of this study indicate that two hypotheses are supported and two are not supported. The relationship between perceived value and intention to continue using the Halodoc app is positive. The risk barrier variable has no effect on perceived value. The complexity variable has no effect on perceived value. Relative benefit has a positive effect on perceived value.